Study on the ERP Implementation Methods on SAP, Oracle NetSuite, and Microsoft Dynamics - Madabattula, Archana (Digital Repository of Theses - SSBM Geneva, 2025)
The research compares implementation methods, success factors, and barriers associated with three major ERP platforms: Microsoft Dynamics, SAP, and Oracle Netsuite. The research intends to assist various businesses in determining which ERP system is most suited to their needs in terms of corporate operations, system implementation governance, and user adoption strategy. Secondary data included article and journal reviews concentrating on best and worst practices in ERP installation, with a comparative approach. The installation procedures for each platform, Sure Step for Microsoft Dynamics, ASAP for SAP, and SuiteSuccess for Oracle NetSuite, were also examined, including their influence on implementation time and amount of customisation, as well as project outcomes. The research demonstrates that Microsoft Dynamics is adaptable and enables both on-premises and cloud implementation, making it ideal for SMEs, although it frequently encounters governance and scope challenges. SAP, on the other hand, thrives in complicated setups that require a high level of configuration; nevertheless, installation projects are typically resource-intensive and time-consuming, especially when there is a user resistance--a nightmare. Oracle NetSuite is simple to adopt via SuiteSuccess and ideal for businesses that want or need to develop rapidly; nevertheless, it can be stiff in other areas because it is not easily configurable to an enterprise's requirements. User participation and change management strategies are recognized as essential success aspects that can ensure user acceptance and satisfaction, particularly when the organization has invested in systems such as SAP, which may necessitate user familiarity. This study adds to the ERP literature by outlining important Microsoft Dynamics governance issue assumptions and providing novel viewpoints on multi-vendor ERP systems. The research also concludes that diverse platform strategies must align with corporate objectives in order to achieve long-term success with such selections. Future studies should look at the integration of AI and post-implementation performance to improve ERP solutions even further. The findings provide practical advice for organizations and practitioners, with an emphasis on customized implementation tactics, governance frameworks, and ongoing user involvement to achieve effective ERP outcomes.